2019
DOI: 10.1007/s00127-019-01746-2
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, suicidal ideation, and mental health care-seeking in central Mozambique

Abstract: Purpose-There is scant research on depressive symptoms (DS), suicidal ideation (SI), and mental health care-seeking in Mozambique. Methods-Generalized estimating equations were used to assess factors associated with DS, SI, and mental health care-seeking among 3080 individuals interviewed in a representative household survey in Sofala and Manica provinces, Mozambique. Results-19% (CI 17-21%) of respondents reported DS in the past year and 17% (CI 15-18%) lifetime SI. Overall, only 10% (CI 8-11%) of respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 63 publications
1
11
0
1
Order By: Relevance
“…Although the nationwide prevalence of mental illness is not well established in Mozambique, previous research has demonstrated rates of depressive symptoms in the population between 14% and 19% (17,18). The difference in estimated prevalence in the general population and our study sample is consistent with reports from other countries that people with MDD are more likely to seek general health services.…”
Section: Mental Disorders In the Study Populationsupporting
confidence: 86%
“…Although the nationwide prevalence of mental illness is not well established in Mozambique, previous research has demonstrated rates of depressive symptoms in the population between 14% and 19% (17,18). The difference in estimated prevalence in the general population and our study sample is consistent with reports from other countries that people with MDD are more likely to seek general health services.…”
Section: Mental Disorders In the Study Populationsupporting
confidence: 86%
“…This suggests that a large burden of depression is missed in existing psychiatric care settings. A recent population-based survey of over 3,000 households conducted by our group additionally showed the high rates of mental health stigma in central Mozambique, as well as treatment gaps for depressive symptoms and suicidal ideation of almost 70% and 90%, respectively (24,25).…”
Section: Introductionmentioning
confidence: 59%
“…This suggests that a large burden of depression is missed in existing psychiatric care settings [ 25 ]. A recent population-based survey of over 3000 households conducted by our group additionally showed the high rates of mental health stigma in central Mozambique, as well as treatment gaps for depressive symptoms and suicidal ideation of almost 70 and 90%, respectively [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%